(untitled) (Journal of Technology and Operations Management, 2023)
The most crucial competitive advantage for any corporate organization is an effective management practices. Making oneself and others successful is one of the most important components of effective management since it involves the management functions of planning, organizing, leading, and controlling all of the organizational units in the organization. The objective of this paper is to create a conceptual framework for management practices and functions based on Islamic principles, not only to assure organizations success but also to ensure that Islamic ethics principles as well as the Islamic values are upheld. It was conceptually discussed that management practices and functions which are conducted in accordance with Islam’s views are applicable to current business practices and the suitability is relevant for modern day business operations.